Children of men - Dinello, Dan (Constellations (Leighton Buzzard, England), 2019)
A mirror of tomorrow, Alfonso Cuarón's visionary Children of Men (2006) was released to good reviews and poor box office but is now regarded by many as a twenty-first-century masterpiece. Its propulsive story dramatizes a dystopian future when an infertile humanity hurtles toward extinction and an African refugee holds the key to its survival. Dinello explores the film's criticism of the pathologies of a reactionary politics that normalize discriminatory hierarchies and perpetuate vast differences in privilege. Children of Men prods us to imagine an egalitarian alternative with a narrative that urges emotional identification with rebels, outcasts, and racial and ethnic outsiders.